2011
DOI: 10.1097/aln.0b013e318223b8b9
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of GSK-3β Mediates Intralipid-induced Cardioprotection against Ischemia/Reperfusion Injury

Abstract: Background Intralipid, a brand name for the first safe fat emulsion for human use, has been shown to be cardioprotective. However, the mechanism of this protection is not known. Here we investigated the molecular mechanism(s) of Intralipid-induced cardioprotection against ischemia/reperfusion injury, particularly the role of GSK-3β and mitochondiral permeability transition pore in this protective action. Methods In-vivo rat hearts or isolated Langendorff-perfused mouse hearts were subjected to ischemia follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
138
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 36 publications
(48 reference statements)
9
138
1
1
Order By: Relevance
“…Phosphorylation of ERK1/2, AKT, and STAT3 represents RISK and SAFE activation 22. In the present study, the phosphorylation of ERK1/2 (Figure 5A), AKT (Figure 5B), and STAT3 (Figure 5C) was found to be increased in I/R‐injured hearts after treatment with gastrin.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Phosphorylation of ERK1/2, AKT, and STAT3 represents RISK and SAFE activation 22. In the present study, the phosphorylation of ERK1/2 (Figure 5A), AKT (Figure 5B), and STAT3 (Figure 5C) was found to be increased in I/R‐injured hearts after treatment with gastrin.…”
Section: Resultssupporting
confidence: 60%
“…In the presence of PD98095 (10 μmol/L),23 an ERK1/2 inhibitor, the protective effects of gastrin on the I/R‐injured hearts were decreased, as determined by measurement of cTnI (Figure 6A), LDH release (Figure 6B), apoptosis (TUNEL assay, Figure 6C), cleaved caspase 3 protein (Figure 6D), and cardiac infarct size (Figure 6E). Correspondingly, the protective effects of gastrin were blocked in the presence of LY294002 (50 μmol/L; AKT inhibitor)22 and S3I‐201 (100 μmol/L; STAT3 inhibitor; Figure 6),24 which proves that the RISK and SAFE pathways are involved in mediating the cardioprotective effects of gastrin.…”
Section: Resultsmentioning
confidence: 87%
“…Intralipid is a solvent for propofol. Although studies have demonstrated that post-ischemic treatment with intralipid had cardioprotective effects against reperfusion injury [28] , previous studies [12] and our preliminary results demonstrated that intralipid itself did not affect hemodynamics or ischemiainduced arrhythmias. Based on these results, we believe that the use of intralipid as a vehicle did not influence the effects of propofol during ischemic conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Activation of the G-protein mechanism leads to smooth muscle contraction, and thus vasoconstriction, via calcium influx [26]. ILE has been shown to alter myocardial calcium homeostasis [20,27], but its effect on calcium levels in vascular smooth muscle has not been well studied. ILE has also been shown to enhance alpha 1 mediated vasoconstriction [28] and reduce endothelium-mediated vasodilation after sustained infusion [29].…”
Section: Discussionmentioning
confidence: 99%